Effects of obesity on dynamic stability control during recovery from a treadmill-induced slip among young adults - Yang, Feng; Kim, JaeEun; Yang, Fei (Journal of biomechanics, 2017)
This study sought to investigate the effects of obesity on falls and dynamic stability control in young adults when subject to a standardized treadmill-induced gait-slip. Forty-four young adults (21 normal-weight and 23 obese) participated in this study. After their muscle strength was assessed at the right knee under maximum voluntary isometric (flexion and extension) contractions, participants were moved to an ActiveStep treadmill. Following 5 normal walking trials on the treadmill, all participants encountered an identical and unexpected slip defined as a perturbation in the anterior direction with the magnitude of 24-cm slip distance and 2.4-m/s peak slip velocity. The trials were categorized as a fall or recovery based on the reliance of the subject on external support following the slip. Compared with the normal-weight group, the obese group demonstrated less relative muscle strength and fell more responding to the slip (78.3% vs. 40.0%, p=0.009). After adjusting the body height and gender, the results indicated that the obese group was 19.1-time (95% confidence interval: [2.06, 177.36]) more prone to a fall than the normal-weight group when experiencing the same treadmill-induced slip. The obese group showed significantly impaired dynamic stability after slip possibly due to the inability of controlling the trunk segment׳s backward lean movement. Obesity measurements explained more slip outcome variance than did the strength measurements (53.4% vs. 18.1%). This study indicates that obesity most likely influences the ability to recover from slip perturbations. It is important to develop interventions to improve the capability of balance recovery among individuals with obesity.